Numerical investigation of ventilation performance of different air supply devices in an office environment. (August 2015) - Chen, Huijuan; Janbakhsh, Setareh; Larsson, Ulf; Moshfegh, Bahram
Abstract: The aim of this study was to compare ventilation performance of four different air supply devices in an office environment with respect to thermal comfort, ventilation efficiency and energy-saving potential, by performing numerical simulations. The devices have the acronyms: Mixing supply device (MSD), Wall confluent jets supply device (WCJSD), Impinging jet supply device (IJSD) and Displacement supply device (DSD). Comparisons were made under identical set-up conditions, as well as at the same occupied zone temperature of about 24.2 °C achieved by adding different heat loads and using different air-flow rates. Energy-saving potential was addressed based on the air-flow rate and the related fan power required for obtaining a similar occupied zone temperature for each device. Results showed that the WCJSD and IJSD could provide an acceptable thermal environment while removing excess heat more efficiently than the MSD, as it combined the positive effects of both mixing and stratification principles. This benefit also meant that this devices required less fan power than the MSD for obtaining equivalent occupant zone temperature. The DSD showed a superior performance on heat removal, air exchange efficiency and energy saving to all other devices, but it had difficulties in providing acceptable vertical temperature gradient between the ankle and neck levels for a standing person. Highlights: Ventilation performance of four different air supply devices in an office environment is studied. The wall confluent jets and impinging jet supply devices behave like a combined mixing and displacement system. The wall confluent jets and impinging jet supply devices provide a good indoor environment and save energy. The displacement supply device provides the highest ventilation efficiency but have problems with local discomfort.